Coexistence of Intracranial and Spinal Cord Cavernous Malformations Predict Aggressive Clinical Presentation - Ren, Jian; Hong, Tao; He, Chuan; Sun, Liyong; Li, Xiaoyu; Ma, Yongjie; Yu, Jiaxing; Ling, Feng; Zhang, Hongqi (Frontiers in Neurology, 2019)
Background: Patients with spinal cord cavernous malformations (CMs) are at increased risk for multiple neuraxis CMs. Few studies focused on the natural history of patients with coexistence of intracranial and spinal cord CMs. Methods: Forty patients who underwent both intracranial and spinal MR imaging from a single center were reviewed retrospectively. American Spinal Injury Association (ASIA) impairment scale was used to evaluate neurological and disability status. Results: The median age of the 40 patients was 40.6 years old (range 9–69), and the male-to-female ratio was 2.1:1. The mean size of the intramedullary lesions was 10.1 ± 5.8 mm (range, 3.0–34.0 mm). Six patients (15%) harbored at least one intracranial lesion. Five of the 6 patients (83.3%) suffered aggressive clinical presentations with severe neurological and disability status; in patients with sporadic spinal CMs, the proportion was 26.5% (9 of 34). Coexistence of intracranial and spinal cord CMs is more likely to follow an aggressive course (P = 0.031, OR = 19.547, 95% CI = 1.322–289.123). In the postoperative long-term follow up, the unfavorable rate of patients with associated intracranial CMs was significantly higher than that of patients with sporadic spinal cord CMs (P = 0.049). Conclusions: The prevalence of associated intracranial CMs in patients with spinal cord CMs was 15%. Coexistence of intracranial and spinal cord CMs is more likely to follow an aggressive course. This study highlights the necessity of intracranial MR imaging for patients with spinal cord CMs to benefit to the predicting prognosis and selection of treatment strategies.